Paracetamol, ibuprofen, and recurrent major cardiovascular and major bleeding events in 19120 patients with recent ischemic stroke - Gonzalez-Valcarcel, Jaime; Hennerici, Michael G. (Stroke, 2016)
Background and purpose: The presumed safety of paracetamol in high-cardiovascular risk patients has been questioned. We determined whether paracetamol or ibuprofen use is associated with major cardiovascular events (MACE) or major bleeding in 19 120 patients with recent ischemic stroke or transient ischemic attack of mainly atherothrombotic origin included in the Prevention of cerebrovascular and cardiovascular events of ischemic origin with terutroban in patients with a history of ischemic stroke or transient ischemic attack (PERFORM) trial. Methods: We performed 2 nested case-control analysis (2153 cases with MACE during trial follow-up and 4306 controls matched on Essen stroke risk score; 809 cases with major bleeding matched with 1616 controls) and a separate time-varying analysis. Results: 12.3% were prescribed paracetamol and 2.5% ibuprofen. Median duration of treatment was 14 (interquartile range 5-145) days for paracetamol and 9 (5-30) days for ibuprofen. Paracetamol, but not ibuprofen, was associated with increased risk of MACE (odds ratio 1.21, 95% confidence interval [CI] 1.04-1.42) or a major bleeding (odds ratio 1.60, 95% CI 1.26-2.03), with no impact of daily dose and duration of paracetamol treatment. Time-varying analysis found an increased risk of MACE with both paracetamol (hazard ratio 1.22, 95% CI 1.05-1.43) and ibuprofen (hazard ratio 1.47, 95% CI 1.06-2.03) and of major bleeding with paracetamol (hazard ratio 1.95, 95% CI 1.45-2.62). Conclusions: There was a weak and inconsistent signal for association between paracetamol or ibuprofen and MACE or major bleeding, which may be related to either a genuine but modest effect of these drugs or to residual confounding.
Gesehen am 04.04.2019